The Existence and Uniqueness of Solution of Duffing Equations with Non-C2 Perturbation Functional at Nonresonance. (30th March 2008) - Ting, Zhou; Wenhua, Huang
Abstract : This paper deals with a boundary value problem for Duffing equation. The existence of unique solution for the problem is studied by using the minimax theorem due to Huang Wenhua. The existence and uniqueness result was presented under a generalized nonresonance condition.